2014
DOI: 10.2495/hpsm140041
|View full text |Cite
|
Sign up to set email alerts
|

Tracking heat-affected zone cracking susceptibility in standard and modified heat treated IN 738 superalloy welds

Abstract: The conditions influencing the phenomenon of heat affected zone (HAZ) cracking during tungsten inert gas (TIG) welding of a gamma-prime (γ') precipitation strengthened nickel-base superalloy, IN 738, is discussed here. The discussion is reinforced with the dependence of the cracking on particle size variation of the γ' precipitates and base alloy hardness. Microstructural analysis of the magnitude of HAZ cracking in the alloy indicates that while resistance to cracking susceptibility is poor in the standard he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The high hardness values might also be due to the very dense or very fine γ′ precipitates in the base metal and in HAZ, together with more γ′ precipitates in the weld filler near the HAZ [25]. It was found that these γ′ precipitates become coarser due to more dispersion by other elements such as aluminium and/or titanium from the base metal into FZ, followed by the formation of a coarser size of γ′ precipitates in this area [26]. Fig.…”
Section: The Post-wlding Heat Treated Inc 738 Lc Ni Superalloymentioning
confidence: 99%
“…The high hardness values might also be due to the very dense or very fine γ′ precipitates in the base metal and in HAZ, together with more γ′ precipitates in the weld filler near the HAZ [25]. It was found that these γ′ precipitates become coarser due to more dispersion by other elements such as aluminium and/or titanium from the base metal into FZ, followed by the formation of a coarser size of γ′ precipitates in this area [26]. Fig.…”
Section: The Post-wlding Heat Treated Inc 738 Lc Ni Superalloymentioning
confidence: 99%